Developing a participatory biosecurity training module for finfish aquaculture in Bangladesh - Papadopoulou, Athina; Worswick, John; Rahman, Md. Habibur; Naher, K.; Rheman, Shafiq; Hossain, Sabrina; Bhuiyan, M.; Nowsher, A.; Alam, Md. Badrul (Centre for Environment, Fisheries and Aquaculture Science, 2024)
Building on the success of the Bangladesh FAO Emergency Centre for Transboundary Animal Diseases (ECTAD) team to develop and implement a very successful biosecurity training module for poultry in the country. Members of the Reference Centre visited Bangladesh to develop similar training modules for the Bangladesh finfish aquaculture sector. The UK FAO Reference Centre for AMR experts worked together with project partners, the Department of Fisheries (DoF), FAO ECTAD team and WorldFish